Question
upstudy study bank question image url

4)) Solve the system of equations. \[ y=x^{2}-6 x+19 \] \( y=-3 x+47 \) 4)) Write the coordinates in exact form. Simplify all fractions and radicals. (

Ask by Campos Rowe. in the United States
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( (-4,59) \) and \( (7,26) \).

Solution

Solve the system of equations \( y=x^{2}-6x+19;y=-3x+47 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=x^{2}-6x+19\\y=-3x+47\end{array}\right.\) - step1: Substitute the value of \(y:\) \(x^{2}-6x+19=-3x+47\) - step2: Move the expression to the left side: \(x^{2}-6x+19-\left(-3x+47\right)=0\) - step3: Calculate: \(x^{2}-3x-28=0\) - step4: Factor the expression: \(\left(x-7\right)\left(x+4\right)=0\) - step5: Separate into possible cases: \(\begin{align}&x-7=0\\&x+4=0\end{align}\) - step6: Solve the equation: \(\begin{align}&x=7\\&x=-4\end{align}\) - step7: Calculate: \(x=7\cup x=-4\) - step8: Rearrange the terms: \(\left\{ \begin{array}{l}x=7\\y=x^{2}-6x+19\end{array}\right.\cup \left\{ \begin{array}{l}x=-4\\y=x^{2}-6x+19\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x=7\\y=26\end{array}\right.\cup \left\{ \begin{array}{l}x=-4\\y=59\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=-4\\y=59\end{array}\right.\cup \left\{ \begin{array}{l}x=7\\y=26\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=-4\\y=59\end{array}\right.\cup \left\{ \begin{array}{l}x=7\\y=26\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(-4,59\right)\cup \left(x,y\right) = \left(7,26\right)\) The solution to the system of equations is \( (x,y) = (-4,59) \) or \( (x,y) = (7,26) \). Therefore, the coordinates in exact form are \( (-4,59) \) or \( (7,26) \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the system of equations, we'll set the two expressions for \( y \) equal to one another: \[ x^{2} - 6x + 19 = -3x + 47 \] Rearranging the equation gives: \[ x^{2} - 3x - 28 = 0 \] Now, factor the quadratic: \[ (x - 7)(x + 4) = 0 \] This gives us the solutions \( x = 7 \) and \( x = -4 \). Next, we'll find the corresponding \( y \)-values. For \( x = 7 \): \[ y = -3(7) + 47 = 26 \] For \( x = -4 \): \[ y = -3(-4) + 47 = 59 \] Thus, the coordinates are: \( (7, 26) \) and \( (-4, 59) \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy